THE POWER OF WOMEN PATRIACHAL CULTURE IN NOVEL GADIS TANGSI by SOEPARTO BRATA AN OVERVIEW OF FEMINIST LITERARY CRITICISM - Martini, Laura Andri Retno (Faculty of Humanities, Diponegoro University, 2015)
The global community understand the different of gender based on biological and social indicators. The biological indicators, such as sex, the reproduction function, as a given and unchangeable factor. In the other side, the social difference leads to the different attitudes of men or women. This difference is in constructed by society. In the long run, the gender message has been mixed with the given factor, and the duty of child bearing is assumed to be the duty for women only